2005
DOI: 10.1002/rmv.461
|View full text |Cite
|
Sign up to set email alerts
|

Trends in dengue diagnosis

Abstract: The conventional diagnosis of dengue virus infections includes the detection of the virus in serum or tissue samples, both by isolation in culture or through detection of specific viral molecules (genome RNA or dengue antigens) and detection of specific anti-dengue antibodies (serology). Isolation of dengue virus provides the most direct and conclusive approach to diagnosis, despite the demand for high-level equipment, technical skills and manpower. However, it is useless in early diagnosis because several day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
70
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(72 citation statements)
references
References 90 publications
(144 reference statements)
1
70
0
1
Order By: Relevance
“…Managing the consequences of hemorrhage can save lives and decrease hospitalization costs (9). A timely diagnosis of the disease also enables health care professionals to exclude other causes of febrile illness which presents with similar clinical symptoms in the acute phase of disease in areas where dengue is endemic (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…Managing the consequences of hemorrhage can save lives and decrease hospitalization costs (9). A timely diagnosis of the disease also enables health care professionals to exclude other causes of febrile illness which presents with similar clinical symptoms in the acute phase of disease in areas where dengue is endemic (9)(10)(11)(12).…”
mentioning
confidence: 99%
“…We can detect acute dengue infections in acute phase sera by means of virus isolation or PCR (8 -10 ) or by detection of circulating dengue nonstructural protein 1 (NS1) 4 (11 ) using an antigen-detection ELISA (12)(13)(14); but commercially available methods (15,16 ) are slow, cumbersome, and costly. They require research resources or simply are not available (NS1 ELISA).…”
mentioning
confidence: 99%
“…9,10,25 Nevertheless, these types of compounds commonly show a low bioavailability, especially for therapeutic uses, the reason why several strategies to overcome this limitation focus on the use of a wide variety of nanocarriers, including liposomes, solid lipid nanoparticles, nanoemulsions and nanocrystals, or polymeric nanoparticles, among others. 26 Liposomal formulations have shown interesting properties in terms of the effective antiviral dose, decreasing the toxic concentrations and enhancing the retention time of the drug in blood circulation (due to pegylation). Experiments in vivo demonstrated that the delivery of iminosugars (all deoxynojirimycin derivatives) via Figure 2.…”
Section: Antiviral Drugsmentioning
confidence: 99%